The Role of Religious Counsellor in KUA, North Tapin District, Tapin Regency in Preventing Early Marriage - Nurul Hafizhah; Nur Falikhah; Muhammad Mabrur (UIN Antasari Banjarmasin, 2023)
South Kalimantan Province is one of the provinces that contributes to a reasonably high number of early marriages in Indonesia. One of the districts with a reasonably high rate of early marriage is Tapin District. Of course, this is a challenge for the government of South Kalimantan to reduce the high rate of early marriage. Religious counselors are one of the spearheads predicted to reduce the high rate of early marriage effectively. This research looks at the critical role of religious educators in suppressing the high rate of early marriage, especially in the North Tapin District, Tapin Regency. This method is field research with data collection, namely observation, interviews, and documentation. The results showed that religious extension workers in Tapin Utara District played an essential role in reducing the number of early marriages. They act as educators, reformers, information straighteners, and unifiers.